The Role of Religious Books in Interfaith Dialogue in Plural Society in Indonesia - Yurulina Gulo (Mahesa Research Center, 2025)
This article aims to describe the role of religious books in interfaith dialogue. Interfaith dialogue is one alternative for overcoming and minimizing disputes and misunderstandings between religious communities. The values written in religion can be used as a reference for such things. This study uses qualitative methods by conducting observations, interviews, and literature studies. The focus of this research is centered on plural societies that have different beliefs. Dialogue between religious communities is very important in plural societies, and one of the foundations of dialogue is the awareness that in religion, especially Christianity, there is a need for peace and unity in a society without being influenced by radicalism in religion. The role of values conveyed through religion can make its adherents appreciate that all creatures, especially humans, must coexist in harmony and peace. The role of the Bible not only provides a foundation for Christian faith, but the Bible understands that humans from other religions need to be attached and respect each other's ideas, beliefs, freedoms, and so on. Thus, diversity in Indonesia can be realized without being separated by religion.